Building cost comparison between conventional and formwork system - Haron, Nuzul Azam; Hassim, Salihudin; Abdul Kadir, Mohd Razali; Jaafar, Mohd Saleh (Penerbit UTM Press, 2005)
The Malaysian construction industry is undergoing a transitional change from an industry employing conventional technology to a more systematic and mechanised system. This new system is now known as the industrialised building system (IBS). This new method of construction can increase productivity and quality of work through the use of better construction machinery, equipment, materials, and extensive pre–project planning. This study is essential since there is no organised body, which can provide the necessary information on the building cost comparison between the conventional system and industrialised building system in Malaysia’s construction industry. The study also addresses the building cost comparison of the conventional system and selected formwork system in the industrialised building system. It details out the building cost comparison between the conventional system and the formwork system and indicates which of the two is cheaper. The data were collected through questionnaire survey and case study, which involved institutional buildings. Through the statistical test ‘t–test’, it is shown that there is a significant difference in cost saving for the conventional system as compared to the formwork system.